ORGANIZATIONAL COMMUNICATION PATTERN OF GARDA DEPAN PT. ASELI DAGADU DJOKDJA IN INHERITING CORPORATE CULTURE - Brigita Luna Anggia Putri; Christina Rochayanti; Kartika Ayu Ardhanariswari (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2019)
PT. Aseli Dagadu Djokdja is a Yogyakarta based alternative souvenir provider that has the slogan